Пролин у растений и клеточных культур кукурузы при действии осмотических стрессов in vitro - Сергеева, Л.Е.; Бронникова, Л.И.; Дыкун, М.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. Young corn inbred line plants and cell cultures, obtained from those lines, were cultivated under salinity (25.0 g/l sea water salts) or water stress (0.8 M mannitol). The role of proline in those variants was investigated. Methods. We added stress compounds to water or ½ Murashige-Skoog medium (for plants) to S1 medium (for cell cultures) and tested corn variants. The free proline levels were estimated on the 14th day of stress pressure. Results. The level of free proline rose in plants, cultivated on nutrition medium with the addition of mannitol and in calli tissues, cultivated under both types of osmotic stresses. The plant proline content elevated after the degradation of proline rich proteins, PRPs. But at the same time cell proline was the product of biosynthesis. Conclusions. The absolute values of proline levels are not indices of plant stress tolerance. Keywords: Zea mays, intact plants, cell culture salinity, water stress, proline.